Conflitos e relações de poderes entre a justiça e os gêneros sexuais: o crime de sedução de menor dentro da literatura jurídica brasileira – 1940-1990 - PEREIRA, Eder Adriano (Universidade Federal do Pará, 2021)
This essay is part of my master's research, which analyzes through twenty procedural sources, filed in the collection of the Centre for Documentation and Research Support ─ CEDAP located at UNESP / AssisSP, the smaller occurred seduction of crime between 1940 with the advent of the Penal Code, by the year 1990 with the establishment of the Child and Adolescent, ECA. This that, in addition to modify the form of law and justice on and this "new customers" in the late 1990s also changed the term "minor" for the children and adolescents, meaning greater attempts and properties of understanding, care , rights and duties to the full development of the same society.